2002
DOI: 10.1073/pnas.122247299
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus type-2 expression of pigmented epithelium-derived factor or Kringles 1–3 of angiostatin reduce retinal neovascularization

Abstract: Neovascular diseases of the retina include age-related macular degeneration and diabetic retinopathy, and together they comprise the leading causes of adult-onset blindness in developed countries. Current surgical, pharmaceutical, and laser therapies for age-related macular degeneration (AMD) rarely result in improved vision, do not significantly prevent neovascularization (NV), and often result in at least some vision loss. To address this therapeutic gap, we determined the efficacy of recombinant adeno-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 48 publications
1
68
0
1
Order By: Relevance
“…The number of such vascular endothelial cell nuclei in eyes treated with rAAV-2/2pedf and rAAV-2/2k1k3 was significantly reduced compared with untreated eyes. 61 For rAAV-2/ Recombinant AAV-mediated gene transfer to the retina F Rolling 2sFlt1 assessment, the vector was intravitreally injected at P2 and retinal neovascularization was quantified on retinal flatmounts following perfusion with dextranconjugated FITC at p19. Eyes injected with AAV-2/2sFlt1 displayed fewer neovascular complexes than PBS-injected eyes.…”
Section: Gene Transfer In Animal Models Of Retinal Degenerationmentioning
confidence: 99%
“…The number of such vascular endothelial cell nuclei in eyes treated with rAAV-2/2pedf and rAAV-2/2k1k3 was significantly reduced compared with untreated eyes. 61 For rAAV-2/ Recombinant AAV-mediated gene transfer to the retina F Rolling 2sFlt1 assessment, the vector was intravitreally injected at P2 and retinal neovascularization was quantified on retinal flatmounts following perfusion with dextranconjugated FITC at p19. Eyes injected with AAV-2/2sFlt1 displayed fewer neovascular complexes than PBS-injected eyes.…”
Section: Gene Transfer In Animal Models Of Retinal Degenerationmentioning
confidence: 99%
“…Intraocular adeno-associated virus (AAV) 2-mediated gene transfer of Pedf also suppressed the retinal and choroidal NV. [43][44][45] Injection of AdPEDF.11 beneath the conjunctiva along the outer border of the sclera resulted in transduction of episcleral cells that produced PEDF on the outside of the eye. 46,47 The PEDF penetrated the sclera, resulting in high levels in the choroid that caused regression of choroidal NV.…”
Section: Pigment Epithelium-derived Factor (Pedf)mentioning
confidence: 99%
“…Similarly, intraocular injection of angiostatin packaged in AAV or lentiviral vectors suppressed retinal and choroidal NV. 45,69,70 Oxford BioMedica UK Ltd (Oxford, UK) has taken advantage of the large capacity of lentiviral vectors to package both endostatin and angiostatin in equine infectious anemia viral vectors. Expression of endostatin and angiostatin suppresses leakage and growth of choroidal NV in mice.…”
Section: Endostatin and Angiostatinmentioning
confidence: 99%
“…Expression of pigment epithelium-derived factor (PEDF) has been shown to suppress ocular neovascularization in several models (Mori et al, 2001a(Mori et al, ,b, 2002Auricchio et al, 2002;Raisler et al, 2002;Gehlbach et al, 2003a) and a phase I trial in patients with neovascular AMD showed promise . Other promising transgenes for treatment of ocular neovascularization include endostatin, which reduces excessive vascular permeability in addition to suppressing neovascularization (Auricchio et al, 2002;Takahashi et al, 2003), angiostatin (Lai et al, 2001a;Raisler et al, 2002;Igarashi et al, 2003), and soluble VEGF receptor 1 (Honda et al, 2000;Lai et al, 2001bLai et al, , 2005Bainbridge et al, 2002;Gehlbach et al, 2003b;Rota et al, 2004).…”
Section: Ocular Gene Therapymentioning
confidence: 99%